The Methodological Crisis in Psychology, the Crisis of Methodology of Psychology, and the Issue of Methodological Entitiness of Psychology - Petrosyan, Gagik (Bulletin of Yerevan University E: Philosophy, Psychology, 2024)
The article discusses the manifestations of the methodological crisis of psychology and the possibilities of its solution. Special attention is paid to the fact that nowadays the crisis of psychology is mostly manifested not by the open conflict of its separate directions, but by the crisis of the methodology of psychology, which can be expressed, for example, by the presence of a crisis in the field of discussion of the problem of the methodological crisis caused by the theoretical fragmentation of psychology. The crisis in methodology of psychology arises primarily because, amid the diversity of psychological theories, a cohesive methodology has historically not been established to precede psychological conceptions. This lack of a unified methodological framework hinders the opportunity to form a cohesive field for considering these conceptions together. In the absence of a unified methodology, discussing the theoretical fragmentation of psychology becomes impossible. Therefore, the unification of psychology must be preceded by the unification of its methodology. A unified methodology is only feasible if it presupposes a form of psychology that is methodologically prior to all historically establish and circulating psychological conceptions. The possibility of such psychology is directly related to the problem of methodological entitiness of psychology, which refers to the existence of psychology independent of all known psychological concepts. The latter acts as a dimension composed of the axes of the possibility of psychological knowledge and the necessity of forming psychological concepts, where all psychological concepts can be combined and considered together.